Teosofi Tariqa and the Principles, Rituals, and Rationality as a Religious Movement - M. Dimyati Huda; Nur Chamid (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2020)
This article seeks to reveal the principles, rituals, and rationality of a religious movement named ‘Teosofi Tariqa,’ a Sufi order that has existed since 1908 in Indonesia. The importance of this research is based on the different perspectives from other religious movements offered by Teosofi Tariqa, and also in terms of religious conflict resolution in this country. This research used a qualitative approach, which relied significantly on several instruments, such as observations, interviews, and documentation for data collection, while the Miles and Huberman versions were used for the analysis. It was discovered that the Teosofi Tariqa in Surabaya promulgates tolerance and diversity principles towards other people regardless of their religions. As a Sufi order, the movement emphasizes mysticism and meditation as a means of submission, obedience, and servitude to the absolute and rational God. It also emphasizes the importance of community services.